2017
DOI: 10.1117/1.nph.4.3.035003
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular function recovery after focal ischemic stroke by enhancing cerebral collateral circulation via peripheral stimulation-mediated interarterial anastomosis

Abstract: Current treatments for ischemic stroke have focused on the administration of a tissue plasminogen activator, although the associated side effects and subsequent reperfusion injury remain challenging. Peripheral electrical stimulation has shed light on therapeutic interventions for ischemia by increasing cerebral blood flow (CBF) to the target region through collateral circulation, although the mechanism remains elusive. Here, a focal photothrombotic ischemic (PTI) stroke was induced in the right hemispheric pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Such activation results in functional and structural protection from impending ischemic stroke, findings that were independently replicated in other labs. [5][6][7][8][9][10] Further, our findings [11][12][13][14][15][16][17][18] (reviewed in Refs. [19][20][21] have demonstrated that such stimulus-based protection is achievable in anesthetized rats, unrestrained behaving rats, and in old rats.…”
Section: Introductionsupporting
confidence: 69%
“…Such activation results in functional and structural protection from impending ischemic stroke, findings that were independently replicated in other labs. [5][6][7][8][9][10] Further, our findings [11][12][13][14][15][16][17][18] (reviewed in Refs. [19][20][21] have demonstrated that such stimulus-based protection is achievable in anesthetized rats, unrestrained behaving rats, and in old rats.…”
Section: Introductionsupporting
confidence: 69%
“…We have used a rat model of cerebral ischemia, a dorsal permanent Middle Cerebral Artery occlusion (pMCAo) that results in cortical infarct and functional deficits 24 h after ischemic onset as assessed by functional imaging, blood flow imaging, neuronal recordings, and histological staining, in addition to behavioral impairments assessed one-week post occlusion 2 . However, applying the same assessment techniques we have demonstrated that intermittent sensory (whisker) stimulation delivered during the hyperacute state post pMCAo as an ‘early’ treatment immediately after pMCAo (+0 h), 1 h or 2 h after pMCAo (+1 h and +2 h respectively) protects the cortex from ischemic stroke damage (see similar findings 3 , 4 ). Beyond the 2 h early protection window, the same sensory stimulation treatment is not protective anymore and could even exacerbate damage if delivered as ‘late’ treatment 3 h (+3 h) after ischemic onset (reviewed in 5 ).…”
Section: Introductionsupporting
confidence: 66%
“…The skin of the scalp was removed from the skull to expose the bregma and the lambda as reference points. The location of the window was at the intersection of the middle cerebral artery (MCA) and anterior cerebral artery, which is associated with primary somatosensory cortex forelimb region (S1FL) and the primary somatosensory cortex hindlimb region (S1HL; anterior/posterior: -1 mm and medial/lateral: 1.5 mm; anterior/posterior: 3 mm; and medial/lateral: 4.5 mm to the bregma), according to a previous study ( Pan et al, 2017 ). The window was drilled to a target size of 4 mm × 3 mm using a dental drill, and saline (Taiwan Biotech Co., Ltd., Taoyuan, Taiwan) was applied each 5 min for cooling.…”
Section: Methodsmentioning
confidence: 99%